Opportunistic contention-based feedback protocol for downlink OFDMA systems with mixed traffic - Patachaianand, Rachod; Sandrasegaran, Kumbesan; Mohd. Ramli, Huda Adibah; Basukala, Riyaj (Springer Link, 2009)
An opportunistic feedback protocol is proposed for orthogonal frequency division multiple access (OFDMA) systems with mixed realtime (RT) and non-realtime (NRT) traffic. This protocol allocates a dedicated feedback channel for each RT user, while it allows all NRT users to compete to send feedback via a contention-based random access feedback channel. The proposed feedback protocol requires a fixed amount of resource to carry feedback from all RT users and some selected NRT users. The probability that NRT users attempt to send feedback is based on two parameters: a channel quality threshold, and the number of subcarriers (or clusters) whose channel quality is above the threshold. Simulation results demonstrate that allocating a dedicated feedback channel for RT user improves the achievable throughput significantly compared with allocating a dedicated traffic channel. For NRT users, the achievable sum rate of the proposed protocol when the number of users is moderate (20-50 users) approaches the ideal case when the channel quality of all users is known at the base station. The sum rate also is close to the ideal case when the number contention minislots per subcarrier is as low as 2 minislot per subcarrier.